Molecular studies for Aphid [Lipaphis erysimi (Kalt.)] resistance in the advanced generation (F4) of the Brassica interspecific hybrid GM-3 × Pusa Swarnim - Desai Pallavi Kumari Onkarnath; Sasidharan N (Environment Conservation Journal)
Globally, rapeseed mustard is the third most important oilseed crop. Lipaphis erysimi, commonly known as the mustard aphid, severely affects the crop, causing significant yield losses and reduced oil content. Breeding for aphid resistance, identifying and validating molecular markers for this trait is, therefore, crucial for developing resistant genotypes. The objective of this study was to develop and phenotype F₄ populations for aphid resistance, identify transgressive segregants, and validate these findings through the use of molecular markers associated with aphid resistance. The entire F4 population and their parents were screened to estimate the Aphid Infestation Index (AII) and their reaction to aphids. Cross of GM-3 x Pusa Swarnim exhibited an AII of 1.33, indicating resistance towards aphids. GM3 showed a high susceptibility with a mean AII of 4.38, while Pusa Swarnim exhibited high resistance with a mean AII of 0.68. Among the entire F4 population, 72 plants were susceptible (AII 3.00-4.00), 14 plants were highly susceptible (AII > 4.00), 90 plants were moderately resistant (AII 2.50-3.00), and 24 plants were resistant (AII 1.00-2.00). At the molecular level, marker analysis of the entire F4 population along with parents was carried out, which revealed that marker SSR OI10-F04, which amplified 432 bp and 206 bp bands from GM-3 and Pusa Swarnim, respectively, showed clear differences between resistant and susceptible plants, whereas another marker, OI10-F06, which amplified a 180 bp band in all F4 plants, did not differentiate between resistance levels and the susceptible one and hence was not analyzed further.  Statistical analyses confirmed the significant association between marker OI10-F04 and aphid resistance as evidenced by an F-value of 140.88, χ² of 0.73, and t-test value of 0.02, supporting its segregation in accordance with Mendelian ratios. This marker holds considerable potential for use in breeding programs aimed at developing aphid-resistant mustard genotypes.